Clinical and Forensic Aspects of Jellyfish Stings - Sara Almeida Saraiva dos Reis Cunha (2022)
Jellyfish are ubiquitous animals and their contact with humans in coastal areas is frequent. These encounters result in a multitude of symptoms, ranging from mild erythema to death. This work aims to review the state-of-the-art regarding pathophysiology, diagnosis, treatment, and relevant clinical and forensic features of jellyfish stings. There are three classes of jellyfish, causing various clinical pictures. Most envenomations result in an erythematous lesion with particular morphological characteristics that may help identify the class of jellyfish responsible. In rare cases, the sting may result in delayed, persistent, or systemic symptoms. Lethal encounters have been described, but most of those cases happened in the Indo-Pacific region, where cubozoans, the deadliest jellyfish class, can be found. The diagnosis is mostly clinical but can be aided by dermoscopy, skin scrapings/sticky tape, confocal reflectance microscopy, immunological essays, among others. Treatment is currently based on preventing further envenomation, inactivating the venom, and alleviating local and systemic symptoms. However, the strategy used to achieve these effects remains under heated debate. Only one antivenom is currently used and covers only one species (Chironex fleckeri). Other antivenoms have been produced experimentally but were not tested on human envenomation settings.